2013
DOI: 10.1371/journal.pone.0059321
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein/Albumin Ratio Predicts 90-Day Mortality of Septic Patients

Abstract: IntroductionResidual inflammation at ICU discharge may have impact upon long-term mortality. However, the significance of ongoing inflammation on mortality after ICU discharge is poorly described. C-reactive protein (CRP) and albumin are measured frequently in the ICU and exhibit opposing patterns during inflammation. Since infection is a potent trigger of inflammation, we hypothesized that CRP levels at discharge would correlate with long-term mortality in septic patients and that the CRP/albumin ratio would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
299
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 346 publications
(311 citation statements)
references
References 40 publications
8
299
0
4
Order By: Relevance
“…Fairclough et al proposed the concept of CRP/Alb ratio22. Otavio et al indicated that CRP/Alb ratio showed predicted mortality in patients in ICU20. Furthermore, Akiyoshy et al demonstrated that CRP/Alb ratio was a prognostic factor in patients with hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fairclough et al proposed the concept of CRP/Alb ratio22. Otavio et al indicated that CRP/Alb ratio showed predicted mortality in patients in ICU20. Furthermore, Akiyoshy et al demonstrated that CRP/Alb ratio was a prognostic factor in patients with hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of CRP and serum albumin is unknown and may have independent prognostic value. A previous study showed that CRP/Alb ratio is an independent risk factor of mortality in patients with sepsis20. Moreover, it has been shown that the C-reactive protein/ Albumin (CRP/Alb) ratio is significantly associated with the outcome of patients with cancer21.…”
mentioning
confidence: 99%
“…27,28 More recently, hypoalbuminemia associated with elevated CRP values has been shown to be a predictor of poor outcome in septic patients. 29 However, confounding factors such as anemia in cancer patients or cancer-related elevated CRP values should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the CRP/albumin ratio has been used to better predict mortality risk in 87 septic patients 19 .…”
mentioning
confidence: 99%